Effects of intestinal flora on polycystic ovary syndrome - Liu, Jiayue; Liu, Ying; Li, Xiaoliang (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. Its clinical characteristics are mainly oligo-ovulation or anovulation, hyperandrogenemia and insulin resistance. PCOS is considered to be one of the main causes of infertility in women of childbearing age, and its pathogenesis is still unclear. Intestinal flora, known as the "second genome" of human beings, is closely related to metabolic diseases, immune diseases and infectious diseases. At the same time, mounting evidence suggests that intestinal flora can regulate insulin synthesis and secretion, affect androgen metabolism and follicular development, and participate in the occurrence of chronic inflammation and obesity. Intestinal flora imbalance is caused by abnormal interaction between intestinal microflora and host cells caused by changes in intestinal microbial diversity, which is involved in the occurrence and development of PCOS. The adjustment of intestinal flora may be a potential direction for the treatment of PCOS.